Design and optimization of the parameters of the key components for reed harvester - Huang, Jicheng; Zhang, Bin; Tian, Kunpeng; Liu, Haolu; Shen, Cheng (International Journal of Agricultural and Biological Engineering, 2022)
In the present, most of the domestic reed harvesters are still in the research and prototype stage, and there is not yet a model with mature technology, strong versatility and mass production. Some modified reed harvesters used in some places can partially solve the reed harvesting problem, but there are problems such as small cutting width, unstable harvesting quality and low operational efficiency that need further improvement. In the study, a reed harvester was designed to integrate with the cutting and conveying. The key components of reed harvester were analyzed to determine the working parameters of the upper stalk-guiding device, the reciprocating double-acting cutter and the three-layer chain conveyor. Then, a quadratic orthogonal rotation combination test was designed to process the date by Design-Expert, where the failure rate, cutting efficiency and conveying rate were taken as the response indexes. An analysis was also made to explore the effects of forward speed, cutting speed, and chain conveying speed on the response index of the reed harvester. A regression mathematical model was established for the response indexes. The response surface method was then selected to implement the multi-objective optimization of the regression model. The results demonstrated that an optimal combination of operation parameters was achieved as follows: the forward speed was 0.85 m/s, the cutting speed was 1.40 m/s, and the chain conveying speed was 1.33 m/s, where the failure rate was 4.17%, the cutting efficiency was 44.21 plants/s, and the conveying rate was 93.60%. The optimized parameters were verified in the field on the reed harvester. In the field test, failure rate, cutting efficiency, and conveying rate were 4.38%, 43.82 plants/s, and 92.55%, respectively. The relative errors with the optimized values were 9.8%, 5%, and 1.1%, respectively. The results of the study provide a theoretical basis for the control of operating parameters and improved design of reed harvesting implements.Keywords: reed, harvester, operation parameters, multi-objective optimization, response surfaceDOI: 10.25165/j.ijabe.20221506.7909Citation: Huang J C, Zhang B, Tian K P, Liu H L, Shen C. Design and optimization of the parameters of the key components for reed harvester. Int J Agric & Biol Eng, 2022; 15(6): 96–103.